Land-based poly-eco-aquaculture of abalone and seaweed in a small scale recirculating system using a recycled freezer container - Rahman, Mohammad Mustafizur; Kadowaki, Shusaku; Linn, Saw Mya; Yamada , Yohei (Fisheries Research Agency, Japan, 2012)
To minimize environmental problems associated with aquaculture, we wanted to develop an abalone and seaweed polyculture approach in a small scale recirculating aquaculture system housed in an air-conditioned recycled freezer container. We conducted two experiments; each used two recirculating systems. Each system consisted of two biofilters and two abalone culture tanks. Each abalone culture tank contained three plastic baskets for abalone. In the first experiment one of the systems also incorporated a protein skimmer (PS) to evaluate its effects on water quality and abalone growth. In the second experiment, the same system was incorporated with both a PS and a seaweed culture tank (PSS) to evaluate their combined effects on water quality and abalone growth. The abalone stocking density was 20 individuals (average weight 5.3-0.08 g and 8.7-1.9 g in the first and second experiment) per basket. Pelleted artificial feed was supplied six days per week at 2.3% of abalone body weight per day. The pH, dissolved oxygen (DO), total inorganic nitrogen (TIN), total inorganic phosphorus (TIP), and bacterial abundance were monitored daily. The duration of first and second experiments were 87 and 70 days. DO concentration was significantly higher in the system with the PS. An opposite trend was observed in TIN concentration and bacterial abundance. PS had no effect on pH or TIP. PSS influenced water quality parameters and bacterial abundance similar to PS except TIP, which was greater in the system with PSS than without. Treatment effects on growth, feed consumption, and FCR were similar in both experiments. Abalone consumed less feed and had significantly higher FCR and lower growth rates in the control. However, feed consumption, FCR and growth rate of abalone were comparatively better in the PSS system than in the PS system. The PSS system was not only better for abalone growth, but also produced an additional crop in the form of seaweed. The system did not discharge waste. Therefore, future abalone culture systems can be focused on this model. However, more research is necessary before extrapolating results to an industrial level.